Vocativity and Dialogue in the Process of Reading for Translation. Issue 1 (April 2021) - Scott, Clive
Abstract : This article sets out to identify those modes of reading likely to make the process of translation optimally fruitful. It opens with the proposition that translation peculiarly has the capacity to transform our habits of reading and, by doing so, to re-empower language. Such a capacity depends on our establishing a vocative (co-participational) relationship with the text to be translated, rather than an accusative one (source text as analysable document). The pursuit of the vocative entails giving prominence to prosodic or paralinguistic features of language, and to the situation of speech, and preferring the notion of sense to that of meaning. The nature of this vocative relationship is further clarified and refined by reference to Martin Buber's Ich und Du (1923). To properly appreciate translation as the multiform and connective activity that it is, we must understand the 'divinity' of Babel's dialogic and dialectical reciprocities rather than see in Babel a condemnation to untranslatability. The article closes with a translation of Rilke's Sonette an Orpheus, I, 26, which in both subject and translational method plays out the foregoing arguments.